The Effect of Gain-Loss Framing Information on Risk Attitude during Coronavirus Disease (COVID-19) Pandemic - Muhamad Adhitya Nugroho; Rini Dharmastiti; Hilya Mudrika Arini (LPPM Universitas Duta Bangsa Surakarta, 2021)
This study aims to identify risk attitude and analyze its changes by presenting information related to COVID-19 pandemic with gain-loss framing. 152 respondents aged 18-23 years, with the status of active undergraduate students or fresh graduates, and stayed in Special Region of Yogyakarta Province, Indonesia, participated in this study. RiBy using lottery choice questionnaire to measure risk attitude in initial condition, it is found that 47% of respondents tend to be risk averse, which is being uncomfortable with risk. 28 selected respondents join the gain-loss framing experiments that present series of video news related to COVID-19 pandemic with predetermined tone (gain or loss). Hypothetical gamble survey based on video news are used to measure risk attitude after the experiment. It is known that gain framing information affects someone to be risk averse, while loss framing information makes someone to be risk seeking or feeling comfortable to any risk in decision making. Media coverage are recommended to use gain framing information to control human behavior and support government's policy in complying health protocols and stay at home during COVID-19 pandemic.